Sparking Creativity in Science Education. (12th March 2021) - Draper, Jenna T.; Freeling, Benjamin S.; Connell, Sean D.
Abstract: World‐class science requires inspiration, so how can we spark creativity in the modern university environment? Creativity does not come automatically: in the modern age, factors from electronic devices to time pressure can stifle creative thought. Yet, to solve the major problems of the future, it will be essential to stimulate creativity in scientific research and teaching. Here, we bring together insights from the literature to offer ways to cultivate creativity in universities. We advocate for creativity at all levels of university culture within which students are embedded, from the students themselves, to teachers, to researchers, and to administrators. We found that, for students, creativity can involve accepting creative coursework and understanding failure; for teachers, it can involve being active mentors and designing creative courses; for researchers, it can involve conscious effort to make room for creative thought within pressured workloads, and researching across disciplines; and for administrators, it can involve relaxing restraints, allowing autonomy over courses, and encouraging cross‐disciplinary learning and research.